CHARACTERIZATION OF AUTOFLUORESCENCE AS AN INDICATOR OF ACTIVATION STATE IN NEURAL STEM CELLS - Nisaa, Rachma Khairun (Journal of Stem Cell Research and Tissue Engineering, 2024)
Recent advancements in stem cell research have uncovered a novel autofluorescence marker pivotal for investigating the dormant state of stem cells. This marker presents a groundbreaking opportunity to monitor the transition of stem cells from a quiescent to an active state, facilitating the identification of cells entering the cell cycle. The primary objective of this research is to comprehensively review this marker's efficacy with the aim of developing therapeutic strategies for generating human nerve cells. A systematic literature search initially yielded 2297 articles on autofluorescence characterization as an indicator of activation state in neural stem cells (NSCs). However, only three articles met the stringent inclusion criteria, underscoring the novelty and scarcity of research in this domain. Autofluorescence, particularly in NSCs, offers a non-invasive approach to studying molecular processes and discerning various activation states, obviating the need for external labels. This technique not only preserves the intrinsic properties of cells but also circumvents biases inherent in traditional labeling methods. Moreover, when coupled with cutting-edge technologies such as Optical Coherence Tomography with Spectral Inverse Analysis (OCSI), it enables precise, real-time monitoring of metabolic alterations in NSCs during their transition from dormancy to activity.